Advantages of mortar-based design for coloured self-compacting concrete - Lopez, Anahi (2009)
The development of coloured self-compacting concrete (C-SCC) opens new fields of application, since it adds attractive alternatives for challenging architectural designs in terms of shapes and colour, to the already versatile aesthetic characteristics of traditional coloured concrete. The benefits of using cement paste or mortar tests as a previous step in SCC design to optimize mixture proportions have been recognized.This paper shows the advantages of using a mortar-based mix design methodology for C-SCC. In addition to rapid and easy determination of the proportions of the mixtures including different types of pigments, cements, mineral additions, and chemical admixtures, the mortar approach enables observation of the effect of pigments on the viscosity of C-SCC and evaluation of specific aspects as the colorimetric parameters, the colour homogeneity and the surface finishing.